THE SEA AS A REPRESENTATION OF THE DIVINE SPIRIT IN THE EYES OF THE AMARYLLIS BY NATALIE BABBITT - Kristyowati, Dyah; Hanun Asyifa, Nurul; Septriani, Hilda (Jurnal Ilmiah Bina Bahasa, 2025)
This article explores how the sea is represented as a manifestation of the divine spirit in Natalie Babbitt’s novel The Eyes of the Amaryllis. The sea, as both a setting and symbolic entity, reflects spiritual, ecological, and emotional dimensions throughout the narrative. Given the increasing urgency of environmental issues, particularly climate change and ecological alienation, this study emphasizes the importance of integrating eco-spiritual insights into literary analysis, especially in children’s literature, which shapes early ethical perspectives. Although prior studies have addressed ecocriticism in children's fiction, few have examined how natural elements like the sea are portrayed as spiritual agents. This research aims to analyze the sea’s divine attributes such as compassion, wrath, and transcendence as presented through the experiences of three generations of characters in the novel. Using a qualitative literary analysis method, the study conducts close readings of narrative passages, character development, and symbolic imagery, applying ecocriticism and spiritual ecology as theoretical frameworks. Findings reveal that Babbitt positions the sea as an active force that challenges anthropocentric views, calls for ecological humility, and invites spiritual reflection. The novel ultimately promotes a reimagined relationship between humans and nature that is rooted in empathy, reverence, and ecological awareness.